1997
DOI: 10.1007/bf02463046
|View full text |Cite
|
Sign up to set email alerts
|

Morphochemical features of sensorimotor cortex and neostriatum neurons in rats with different levels of alcohol preference

Abstract: This paper reports interferometric studies of the contents and concentrations of proteins in the cellular structures of neurons of the sensorimotor cortex (layers III, V) and in the region of the caudate nucleus of the neostriatum (Golgi type II cells) in Wistar rats with high, intermediate, and low levels of ethanol preference. The greatest differences between groups of animals in terms of cell size and protein metabolism were seen in the cortex. Along with measures correlating with initial ethanol preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies of protein metabolism measures in hippocampus and amygdala neurons using a quite complex behavioral model [12] revealed significant differences in the resuits as compared with those using simple models. This leads to interest in studying the state of protein metabolism in neurons of layers III and V of the sensorimotor cortex in rats with difference learning abilities in conditions of a similar complex food-procuring model, especially since previous studies have demonstrated that synaptic neurons have initially higher levels of cytochemical heterogeneity as compared with structures such as the eaudate nucleus, hippocampus, and basolateral nucleus of the amygdala [6,14]. This leads to interest in studying the state of protein metabolism in neurons of layers III and V of the sensorimotor cortex in rats with difference learning abilities in conditions of a similar complex food-procuring model, especially since previous studies have demonstrated that synaptic neurons have initially higher levels of cytochemical heterogeneity as compared with structures such as the eaudate nucleus, hippocampus, and basolateral nucleus of the amygdala [6,14].…”
mentioning
confidence: 99%
“…Studies of protein metabolism measures in hippocampus and amygdala neurons using a quite complex behavioral model [12] revealed significant differences in the resuits as compared with those using simple models. This leads to interest in studying the state of protein metabolism in neurons of layers III and V of the sensorimotor cortex in rats with difference learning abilities in conditions of a similar complex food-procuring model, especially since previous studies have demonstrated that synaptic neurons have initially higher levels of cytochemical heterogeneity as compared with structures such as the eaudate nucleus, hippocampus, and basolateral nucleus of the amygdala [6,14]. This leads to interest in studying the state of protein metabolism in neurons of layers III and V of the sensorimotor cortex in rats with difference learning abilities in conditions of a similar complex food-procuring model, especially since previous studies have demonstrated that synaptic neurons have initially higher levels of cytochemical heterogeneity as compared with structures such as the eaudate nucleus, hippocampus, and basolateral nucleus of the amygdala [6,14].…”
mentioning
confidence: 99%